A Feasible Central Limit Theory for Realised Volatility Under Leverage. - Barndorff-Nielsen, O; Shephard, N (Nuffield College (University of Oxford), 2004)
In this note we show that the feasible central limit theory for realised volatility and realised covariation recently developed by Barndorff-Nielsen and Shephard applies under arbitrary diffusion based leverage effects. Results from a simulation experiment suggest that the feasible version of the limit theory performs well in practice.